Epidemiological Realities of Alcoholic Liver Disease: Global Burden, Research Trends, and Therapeutic Promise - Xiao, Jia; Wang, Fei; Wong, Nai-Kei; Lv, Yi; Liu, Yingxia; Zhong, Jiajun; Chen, Shuaiyin; Li, Wei; Koike, Kazuo; Liu, Xiaowei; Wang, Hua (Gene Expression, 2020)
Globally, alcohol consumption contributes to more than 3 million deaths each year. While much of its ramifications is preventable, a coherent public health discourse on how to limit alcohol-related harm has been overdue. By synthesizing information from national and global databases, we show in this analysis that alcohol consumption level and alcohol-attributable burden of diseases, particularly alcoholic liver disease (ALD), are intimately linked to national income distribution, cultural norms, religion, sex, age, and health status. Prevalence and burden of ALD are positively associated with economic standing in most countries, which necessitate active governmental control via cost-effective policies, such as the best buys proposed by the World Health Organization. To date, a number of critical questions remain unanswered over the molecular mechanisms underlying ALD pathophysiology; the insights gained thereof should provide new opportunities for the advancement of novel diagnostic and management strategies. In comparison with other prevailing liver diseases (e.g., viral hepatitis and nonalcoholic fatty liver disease), governmental support to ALD investigation has been sluggish in most Western countries and China, resulting in a dearth of breakthroughs on both the basic and clinical research fronts in the past decades. Emerging foci of clinical trials for ALD therapy include empirical use of probiotics, antioxidants, growth factors, monoclonal antibodies against key inflammatory mediators, and technology-enhanced behavioral interventions. In this article, we seek to provide a comprehensive analysis on the progress and challenges in tackling ALD as a global health problem, with particular emphasis on global disease burden, socioeconomic influences, research trends, government roles, and future therapies.